2024
DOI: 10.3389/fgene.2024.1327243
|View full text |Cite
|
Sign up to set email alerts
|

Historical evolution of cancer genomics research in Latin America: a comprehensive visual and bibliometric analysis until 2023

Ivan David Lozada-Martinez,
Luz Miryam Lozada-Martinez,
Andrés Cabarcas-Martinez
et al.

Abstract: Background: Cancer genomics, as an interdisciplinary research area within the Global Cancer Research agenda, genomics and precision medicine, its important in research and clinical practice in Latin America. To date, there has been no study investigating evolution of this area in this region. The aim of this study was to evaluate for first time, the historical evolution of cancer genomics research in Latin America.Methods: Bibliometric cross-sectional study of documents on cancer genomics published by Latin Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… 22 ) However, growth in research from 1887 to the 1950s was modest. Since then, compared with other medical disciplines, 17 , 18 ) the annual growth rate in this area of research has been low, primarily focusing on countries where blue zones have been described, possibly facilitating the design and execution of studies owing to access to the target population. Nevertheless, the research gap between regions is evident, as indicated by the distribution of publications according to Lotka's law, where 85% of the identified authors have published only up to two documents, suggesting occasional research or publication rather than massive centenarian research groups worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 ) However, growth in research from 1887 to the 1950s was modest. Since then, compared with other medical disciplines, 17 , 18 ) the annual growth rate in this area of research has been low, primarily focusing on countries where blue zones have been described, possibly facilitating the design and execution of studies owing to access to the target population. Nevertheless, the research gap between regions is evident, as indicated by the distribution of publications according to Lotka's law, where 85% of the identified authors have published only up to two documents, suggesting occasional research or publication rather than massive centenarian research groups worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, Scopus includes >15,000 indexed medicine journals and has been previously used to perform bibliometric analyses. 17 , 18 )…”
Section: Methodsmentioning
confidence: 99%